2020
DOI: 10.1002/acr.23918
|View full text |Cite
|
Sign up to set email alerts
|

Different Phenotypes of Osteoarthritis in the Lumbar Spine Reflected by Demographic and Clinical Characteristics: The Johnston County Osteoarthritis Project

Abstract: ObjectiveTo determine if associations between demographic and clinical characteristics and appendicular joint osteoarthritis (OA) reflect different phenotypes of OA in the lumbar spine.MethodsParticipants were from the Johnston County OA Project. Demographic information consisted of age, sex, and race (white and African American), and clinical characteristics consisted of body mass index (BMI), low back pain and injury, and knee, hip, and hand OA. Participants were categorized as having spine OA, facet joint O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Both DSN and OST were dichotomized as absent (none) or present (mild, moderate, or severe). Our prior analyses have examined different cut-offs for defining DSN and OST without any significant change in the findings [ 5 , 6 , 9 11 ]. The intra-rater reliability of this radiologist for the spine features has been reported previously with weighted kappa scores of 0.89 for DSN, 0.90 for OST, and 0.73 for FOA [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both DSN and OST were dichotomized as absent (none) or present (mild, moderate, or severe). Our prior analyses have examined different cut-offs for defining DSN and OST without any significant change in the findings [ 5 , 6 , 9 11 ]. The intra-rater reliability of this radiologist for the spine features has been reported previously with weighted kappa scores of 0.89 for DSN, 0.90 for OST, and 0.73 for FOA [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…FOA was graded as absent or present at each lumbar level, while DSN and OST were graded in a semiquantitative fashion (0 = none, 1 = mild, 2 = moderate, and 3 = severe). Spine OA was defined as the presence of at least mild OST and mild DSN at the same vertebral level (23,24), which is similar to studies that define spine degeneration with the Kellgren/Lawrence (K/L) atlas (13,17). Spondylolisthesis was graded based on the translation of the vertebrae relative to the diameter of the affected intervertebral disc space, with 0 = no listhesis, 1 = ≤25%, 2 = 26-50%, 3 = 51-75%, 4 = 76-100%, and 5 = >100% translation.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is evidence suggesting knee OA and low back pain commonly co-exist [ 24 ] and low back pain has been identified as a risk factor for the development of knee pain in older adults [ 35 ]. A recent study also found the presence of radiographic knee OA was associated with all phenotypes of spinal OA (odds ratios ranging from 1.8 to 4.3) [ 36 ], which may represent the spinal changes found in LSS.…”
Section: Introductionmentioning
confidence: 98%